Morphology features of molybdenum carbide synthesized by DC arc discharge plasma in air; IOP Conference Series: Materials Science and Engineering; Vol. 971 : International Conference on Modern Trends in Manufacturing Technologies and Equipment (ICMTMTE) - Vasiljeva (Vassilyeva) Yu. Z. Yuliya Zakharovna; Pak A. Ya. Aleksandr Yakovlevich; Yakich T. Yu. Tamara Yurievna; Mamontov G. Ya. Gennady Yakovlevich (2020, 2020)
Title screen